2019
DOI: 10.1021/acsmedchemlett.9b00457
|View full text |Cite
|
Sign up to set email alerts
|

Antimalarial N1,N3-Dialkyldioxonaphthoimidazoliums: Synthesis, Biological Activity, and Structure–activity Relationships

Abstract: Here we report the nanomolar potencies of N 1 ,N 3dialkyldioxonaphthoimidazoliums against asexual forms of sensitive and resistant Plasmodium falciparum. Activity was dependent on the presence of the fused quinone-imidazolium entity and lipophilicity imparted by the N 1 /N 3 alkyl residues on the scaffold. Gametocytocidal activity was also detected, with most members active at IC 50 < 1 μM. A representative analog with good solubility, limited PAMPA permeability, and microsomal stability demonstrated oral effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…In an earlier investigation, we verified that several series 1 analogues generated hydrogen peroxide via redox cycling in an in vitro horseradish peroxidase-phenol red assay . To determine if this phenomenon also occurs in mycobacterial cultures, we monitored ROS production using CellROX Green Reagent (Invitrogen).…”
Section: Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…In an earlier investigation, we verified that several series 1 analogues generated hydrogen peroxide via redox cycling in an in vitro horseradish peroxidase-phenol red assay . To determine if this phenomenon also occurs in mycobacterial cultures, we monitored ROS production using CellROX Green Reagent (Invitrogen).…”
Section: Resultsmentioning
confidence: 81%
“…In all, 80 compounds were synthesized and their structures are presented in Table . Of these, several ( 4 – 37 in series 1, 66 – 70 in series 4) have been synthesized and screened for antiplasmodial activity . The reported synthetic pathways were employed to obtain the other compounds in series 1–4 (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the identification of compound 77 as a potent multistage anti‐plasmodial agent, Haynes and co‐workers sought to explore whether related anti‐cancer agents including compound 78 , which are structurally related to sepantronium bromide, could be useful anti‐plasmodial lead compounds . A subsequent SAR study revealed that lipophilic alkyl N1/N3 substituents were critical for activity, with compound 79 displaying good in vitro activity with high water solubility and microsomal stability.…”
Section: Antimalarial Agentsmentioning
confidence: 99%
“…This translated into moderate in vivo activity following oral administration in a humanized mouse model of malaria. This low‐level activity was likely as a result of its relatively low oral bioavailability and a short biological half‐life, whose optimisation will likely constitute the next phase of advancement of this class …”
Section: Antimalarial Agentsmentioning
confidence: 99%